2019
DOI: 10.1038/s41467-019-09229-3
|View full text |Cite
|
Sign up to set email alerts
|

Breeders that receive help age more slowly in a cooperatively breeding bird

Abstract: Helping by group members is predicted to lead to delayed senescence by affecting the trade-off between current reproduction and future survival for dominant breeders. Here we investigate this prediction in the Seychelles warbler, Acrocephalus sechellensis, in which mainly female subordinate helpers (both co-breeders and non-breeding helpers) often help dominants raise offspring. We find that the late-life decline in survival usually observed in this species is greatly reduced in female dominants when a helper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(171 citation statements)
references
References 74 publications
4
154
0
Order By: Relevance
“…The finding that helpers compensate for senescent declines in provisioning rate and offspring survival of dominant females extends the results of a previous study on Seychelles warblers (21), which showed that having helpers was associated with higher late-life survival and delayed senescence for dominant females. A similar effect has also been described for Alpine marmots (Marmota marmota) (35).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The finding that helpers compensate for senescent declines in provisioning rate and offspring survival of dominant females extends the results of a previous study on Seychelles warblers (21), which showed that having helpers was associated with higher late-life survival and delayed senescence for dominant females. A similar effect has also been described for Alpine marmots (Marmota marmota) (35).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the fact that young dominant females show higher provisioning rates than young dominant males means that there is more scope for age-dependent declines in provisioning rates for dominant females. In contrast, incubation attendance -another energetically demanding aspect of parental care -does not decline in older females in the Seychelles warbler (21). An explanation for this may be that there is strong selection against reductions in incubation attendance because lower incubation attendance is associated with a higher risk of egg predation and thus failure of the entire reproductive attempt in this species (29).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is consistent with our results. Further evidence is also beginning to accrue elsewhere that sociality may have an important role in driving patterns of senescence beyond the remits of ‘grandmothering’ 27 28. .…”
Section: Mainmentioning
confidence: 99%
“…In many such cases, this appears to be due to compensatory care or "loadlightening." This is the phenomenon whereby the help provided by helpers allows other group members to reduce their own investment and thereby presumably enhance their survival (and thus the helper's future indirect benefits; Mumme et al, 1989) at the cost of the helper's current reproductive success (Crick, 1992;Heinsohn, 2004;Russell et al, 2007;Hammers et al, 2019). There remain, however, cases in which no discernable fitness effects of helping have been identified (Leonard et al, 1989;Magrath and Yezerinac, 1997).…”
Section: Introductionmentioning
confidence: 99%